The Authority of The Indonesian National Police (POLRI) In Conducting Seizures of Evidence without Court Approval In Criminal Cases - Firmansyah Firmansyah; Ni Ketut Wiratny; Erikson Sihotang (Al-Makki Publisher, 2025)
Law enforcement in Indonesia involves an important role for the Indonesian National Police (POLRI), including in the process of confiscating evidence. However, there are questions regarding the authority of investigators to seize evidence without court approval. This research aims to analyze the authority of POLRI investigators in confiscating evidence without court approval and the responsibility of investigators for confiscated evidence. The research method used is normative research by relying on primary legal materials in the form of laws and regulations, as well as secondary legal materials in the form of related literature. The analysis is done descriptively, systematically, and argumentatively to provide a comprehensive understanding of this issue. The results show that investigators have the authority to confiscate evidence in a caught red-handed situation without having to obtain permission from the court. This is regulated in the Criminal Procedure Code (KUHAP) which provides a legal basis for investigators to take such action. However, the responsibility of investigators in the storage, maintenance and return of evidence to the rightful parties remains an important aspect that needs to be considered. This research concludes that the authority of investigators to seize evidence without court approval can be exercised under certain conditions. However, the investigator's responsibility in managing evidence is crucial to ensure the validity of the legal process. This research is expected to contribute to the development of criminal procedure law in Indonesia, as well as increase understanding of the roles and responsibilities of POLRI in the law enforcement process.